Trioká xohã – Caminhar guerreiro: a retomada dos Pataxó de Gerú Tucunã - Gonçalves, Antônio Augusto Oliveira (2022)
This thesis focuses on the retaking of the Pataxó in Gerú Tucunã, in the municipality of Açucena (MG) – Vale do Rio Doce. The people of Tucunã went through a series of walks between the extreme south of Bahia and Tucunã: from mother village of Barra Velha (BA) they moved in the late 1970s to the Fazenda Guarani Indigenous Land, in Carmésia (MG); from there they moved to Aracruz, Espírito Santo, where they lived with Tupinikim people from the Pau-Brasil village. They returned to Minas in the 1980s and took a new walk, in 2010, from Fazenda Guarani to the territory of Tucunã, where they were looking for fertile land for their swiddens and for reforestation. Populating the socius with plant species is a necessary condition to attract the presence of caboclos in the territory, seeking spiritual protection from their ancestors, one of the main reasons that moved the Pataxó warriors to Açucena. In this complex intertwining of the branches (ramas) with the old trunks (troncos velhos), of the Pataxó of today with their ancestors, the warrior walk (trioká xohã) of the people of Tucunã emerges. Trioká brings back what drives it, that is, the spirituality of the caboclos, the return to the warrior’s language (the Patxôhã), the walks and stories of the ancients. Following the trail of the old trunks (troncos velhos), we come across certain narratives and elders spread out in different pataxí’p (pataxó villages) who tell them to relatives and researchers. The Pataxó of Tucunã themselves carried this ethnography to other Pataxó territories, in Mirapé, Barra Velha and Naô Xohã. When walking along these paths, it is seen that the awãkã’p (Pataxó stories), less than closed in on themselves, circulate in certain people, in the pataxí’p and through txihi (Pataxó) spirituality. Not everyone knows all the narratives, it is necessary to wander in a web of sociality and spokespersons authorized to narrate them. I seek to describe, through these different paths, the forms of resistance in the retaking, the trioká xohã of the Pataxó.